Respuesta :
Answer:
14x+3=8x+3
14x+3 -3 = 8x+3 -3
Cancels out the 3
14x = 8x
14x - 8x = 8x -8x
Cancels out the 8x
14x = 0
x = 0
Step-by-step explanation:
Andre should have collected the like terms in order to have all the variables x on one side before taking the difference.
Inequality expression
Given the inequality expression solved by andre expressed as:
14x + 3 ≤ 8x + 3
Simplify to have:
14x - 8x ≤ 3-3
6x ≤ 0
x ≤ 0
Hence andre should have collected the like terms in order to have all the variables x on one side before taking the difference.
Learn more on inequality here: https://brainly.com/question/24372553